EVALUASI MANAJEMEN BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SDN KECAMATAN LABUHAN RATU BANDAR LAMPUNG - Marini, Marini (UNISAN JURNAL, 2024)
The purpose of this study was to determine the stages of curriculum development in SDN Labuhan Ratu. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographical location in the form of a location plan and environmental conditions, the school's vision, mission, strategy and motto as well as the condition of human resources at SDN Labuhan Ratu. Interviews were conducted for the work culture and work motivation of SDN Labuhan Ratu teachers. Based on the results of the description that has been described, the management of work culture and work motivation not only affect teacher performance, but also affect other factors such as guidance and counseling, student achievement, student learning activities and so on. Given the limitations of data and knowledge sources, the authors examined the relationship between work culture and work motivation with teacher performance.